There John Bull might be seen in all his glory: cross-Channel tourism and the British Army of Occupation in France, 1815–1818. Issue 2 (3rd May 2020) - Reynolds, Luke
ABSTRACT: Between 1815 and 1818, large portions of north-eastern France were occupied by a coalition of European allies. This Army of Occupation, arguably the first of its kind, was created to strengthen Louis XVIII's rule and prevent another uprising like Napoleon's 100 Days. This article argues that, in addition to preserving peace and reincorporating France in the European Congress System, the Army of Occupation was crucial to the reestablishment of cross-Channel tourism between Britain and France and the thawing of relations between those two nations on an individual, as well as governmental, level. Employing a variety of primary sources from both sides of the Channel, it explores military events such as Grand Reviews and race days as well as a variety of civil entertainments, demonstrating that those areas occupied by the British Army served as a physical halfway house and the very idea of the occupation served as a mental halfway house for British civilians, allowing them to feel safe in what had, for the past quarter-century, been enemy territory. This safety then directly translated to economic and cultural exchange, guaranteeing that the peace that the Army of Occupation was designed to create lasted much longer than the occupation itself.